ANALYSIS OF THE PHENOMENA OF THE MASS JUDGMENT FROM A LEGAL SOCIOLOGICAL POINT OF VIEW - Octavia Zulkarnain (Sekolah Pascasarjana Universitas Swadaya Gunung Jati, 2023)
The act of taking the law into your own hands (eigenrichting) is a disgraceful act and also violates the laws in force in Indonesia. Vigilante is referred to from the Dutch language, namely